Preliminary Analysis of the Physics Enrichment Book Design-Edupark Hot Waterboom Solok Selatan Integrated Inquiry Learning Model - Sri Nilam Sari; Hamdi Rifai (Physics Learning and Education, 2023)
Hot Waterboom Solok Selatan is one of the tourist destinations that is often visited by people on vacation. However, visits to these attractions are only for traveling, taking pictures, and playing. They do not realize that tourist attractions can also be used as learning resources. This study aims to determine the needs of teaching materials that are in accordance with the background of students and their environment. This research is a preliminary study of the research and development method using the Plomp model, which consists of student analysis, teacher analysis, and analysis of physics concepts. The data in this study were obtained from the results of needs analysis through interviews with two physics teachers and 38 students at SMAN 3 Solok Selatan. The results obtained from the students' environment, there is a tourist attraction, namely Hot Waterboom Solok Selatan. After direct observation to the tourist attraction, many physics concepts were found. From the results of the learning style questionnaire, students are more dominant visual learning style, so suitable teaching materials in the form of print media such as books. From the results of teacher interviews, the teaching materials used have not been integrated with eduparks and have not been equipped with learning models. The inquiry learning model is a model that is in accordance with the independent curriculum because learning is student centered and involves students actively discovering concepts. Based on the curriculum analysis, it is found that the physics materials on tourist attractions are not ordered, so the type of book that is suitable is an enrichment book. Enrichment book is a flexible type of book because it does not depend on the curriculum. It can be concluded that it is necessary to design a physics edupark enrichment book Hot Waterboom Solok Selatan integrated Inquiry Learning model for senior high school students.